Manajemen Strategi Pengelolaan SMP Al-Azhar Syifa Budi Parahyangan Kabupten Bandung Barat - Saepudin, Asep; Jahari, Jaja; Sulhan, Moh. (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2020)
This research is motivated by the existence of strategic issues in the field of education in Bandung Barat Regency, including the provision of quality and affordable education to the public has not been fully realized, and the condition of educators has not been arranged for all levels of education. Compared to Al-Azhar Middle School Syifa Budi Parahyangan with the results of â€œexcellentâ€ or very good accreditation. The purpose of this study was to determine the description of strategy management concept in the management of Al-Azhar Syifa Budi Parahyangan Middle School in Bandung Barat Regency. According to Fred R. David. The concept of strategy management is the art and science of formulating, implementing, and evaluating cross-functional decisions that enable organizations to achieve goals. This research uses a qualitative approach with descriptive methods. The results showed that: Analysis of strategy formulation, strategy implementation, and Strategy Evaluation at Al-Azhar Middle School Syifa Budi Parahyangan were in accordance with the concept of strategy management. Thus the concept of strategy management can be recommended to be implemented in an organization, both profit organizations or non-profit organizations such as educational organizations.